Hypnosis in Breast Cancer Care: A Systematic Review of Randomized Controlled Trials. (January 2015) - Cramer, Holger; Lauche, Romy; Paul, Anna; Langhorst, Jost; Kümmel, Sherko; Dobos, Gustav J.
Introduction . Many breast cancer patients and survivors experience pain and emotional stress related to their disease, its diagnostic procedures, or treatment. Hypnosis has long been used for the treatment of such symptoms. The aim of this review was to systematically assess the effectiveness of hypnosis in women with breast cancer, breast cancer survivors, and in women undergoing diagnostic breast biopsy. Methods . PubMed, Scopus, the Cochrane Library, PsycINFO, and CAMBASE were screened through February 2014 for randomized controlled trials (RCTs) of hypnosis in women with breast cancer or undergoing diagnostic breast biopsy. RCTs on postmenopausal women without a history of breast cancer were also eligible. Primary outcomes were pain, distress, fatigue, nausea/vomiting, and hot flashes. Safety was defined as secondary outcome measure. Risk of bias was assessed by 2 reviewers independently using the Cochrane Risk of Bias Tool. Results . Thirteen RCTs with 1357 patients were included. In women undergoing diagnostic breast biopsy (3 RCTs), hypnosis positively influenced pain and distress; 1 RCT on breast cancer surgery found effects of hypnosis on pain, distress, fatigue, and nausea. For women undergoing radiotherapy (3 RCTs), hypnosis combined with cognitive–behavioral therapy improved distress and fatigue. In 3 RCTs on women with and without a history of breast cancer experiencing hot flashes, hypnosis improved hot flashes and distress. Three RCTs on women with metastatic breast cancer found effects on pain and distress. Conclusions . This systematic review found sparse but promising evidence for the effectiveness of hypnosis in breast cancer care. While more research is needed to underpin these results, hypnosis can be considered as an ancillary intervention in the management of breast cancer–related symptoms.